(untitled) (Washington, D.C., 2008)
Contents: lessons from the development of silicon valley and its entrepreneurial support networt for Japan; the emergence of Hsinchu science park as an IT cluster
Keywords: Industrial clusters,Khu công nghiệp; Asia,Châu Á